2023
DOI: 10.3389/fneur.2023.1146875
|View full text |Cite
|
Sign up to set email alerts
|

Case report: A novel STXBP1 splice variant and the landscape of splicing-involved STXBP1-related disorders

Abstract: STXBP1 variants are one of the most common genetic causes of neurodevelopmental disorders and epilepsy, wherein STXBP1-related disorders are characterized by neurodevelopmental abnormalities in 95% and seizures in 89% of affected patients. However, the spectrums of both genotype and phenotype are quite wide and diverse, with a high baseline variability even for recurrent STXBP1 variants. Until now, no clear genotype–phenotype correlations have been established and multiple disease mechanisms have been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although LEV did lead to a reduction in seizure frequency, there was no observed difference in achieving seizure freedom [60]. A few case reports anecdotally state that levetiracetam has benefits as well [42,61]. In contrast, a larger-scale analysis of patients with STXBP1 by Xian et al found that LEV had an odds ratio <1 in reducing seizure frequency and maintaining seizure freedom, despite being one of the most prescribed medications.…”
Section: Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Although LEV did lead to a reduction in seizure frequency, there was no observed difference in achieving seizure freedom [60]. A few case reports anecdotally state that levetiracetam has benefits as well [42,61]. In contrast, a larger-scale analysis of patients with STXBP1 by Xian et al found that LEV had an odds ratio <1 in reducing seizure frequency and maintaining seizure freedom, despite being one of the most prescribed medications.…”
Section: Treatmentmentioning
confidence: 95%
“…Splice site variants in patients with STXBP1-related disorders were also reviewed to look for a potential genotype/phenotype correlation. Wang et al [42] looked at 54 canonical splice variants from Clin Var and used splice AI to predict potential splicing changes. Canonical variants were found to cause frameshift or deletion effects, presenting with a phenotype seen in PTV/del variants by Xian et al…”
Section: Genotype/phenotype Correlationmentioning
confidence: 99%